Advancing photoelectrochemical systems for sustainable energy and chemical production: challenges and opportunities - Zhaoyi Xi; Mingzhao Liu (npj Materials Sustainability)
Abstract Photoelectrochemical (PEC) systems offer a promising approach to harness solar energy for producing essential chemicals and sustainable fuels. This perspective highlights their potential for generating hydrogen, oxygen, chlorine, ammonia, hydrogen peroxide, and carbon-based fuels. It also discusses key challenges, such as efficiency, selectivity, and scalability, as well as recent advances in catalyst design and system optimization that enhance practicality and promote real-world adoption.